Supportive campuses and first-generations-student learning outcomes. Issue 2 (20th May 2019) - Wright, Brian
Abstract : Purpose: The purpose of this paper is to analyze the relationship between supportive campus measures and student learning outcomes for first-generation students and non-first generation students to determine if variances are present. A lack of social capital of first generation when compare to non-first-generation students is theorized to be a contributing factor driving differences between the two groups. Design/methodology/approach: Research survey design using penalized regression methods to quantify differences between groups. The analysis used 10 years of student engagement data. Findings: Final analysis showed that first-generation student outcomes had little to no significant connection with the administrative focused aspects of the campus environment as compared to non-first-generation that represented highly significant relationships. This results supports the theory that first-generation students may simply be unaware of how to leverage these resources do to social capital disadvantages. Practical Implications: The result suggests that universities should reconsider first-generation programs to ensure that they have the capability to address first-generation students' lack of social capital. The primary method by which social capital is generated is through networking or peer groups expansion. Consequently, first-generation students might benefit greatly from student mentors that are not first-generation students to help aid in the transition to college as compared to participating in programs that group and isolate first-generation students together. Originality/value: Very few studies have attempted to use social capital as a theoretical framework to explain differences in how first-generation and non-first-generation student learning outcomes relate to campus engagement variables. Moreover, no studies have used both penalized regression and bootstrap validation in addressing this issue, making the study original in design and analysis.